Proceedings of the 30th International Symposium on Automation and Robotics in Construction and Mining (ISARC 2013): Building Th 2013
DOI: 10.22260/isarc2013/0120
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Modeling of Pipes within Point Clouds

Abstract: Three-dimensional models are in increasing demand for design, maintenance, operations and construction project management. Point-clouds are the main output of automatic data collection using laser-scanners and photogrammetric technologies. Pipe-works may comprise 50% of the value of important construction projects such as industrial and research facilities. We have developed a practical and cost-effective approach, based on the Hough-transform and judicious use of domain constraints, to find, recognize and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Hough transform finds shape parameters to best describe the provide data for object generation from PCD. Researchers have shown how this method could be applied to detect pipes and other cylindrical elements [37][38][39]. It can also be used to estimate shape parameters from a PCD with the prior shape knowledge from the corresponding DI [40].…”
Section: Classic Computer Vision Algorithmsmentioning
confidence: 99%
“…Hough transform finds shape parameters to best describe the provide data for object generation from PCD. Researchers have shown how this method could be applied to detect pipes and other cylindrical elements [37][38][39]. It can also be used to estimate shape parameters from a PCD with the prior shape knowledge from the corresponding DI [40].…”
Section: Classic Computer Vision Algorithmsmentioning
confidence: 99%
“…For industrial specific object recognition, some of the popular methods found in the literature are based on voxel connectivity [12][13][14], 2D primitive fitting [15][16][17][18], classifier training [19], and feature and shape descriptor matching [20][21][22][23]. Although a variety of approaches exist, all are negatively impacted by unnecessarily cluttered search spaces.…”
Section: Industrial Object Recognitionmentioning
confidence: 99%